A Literature Review on Teaching Ethical Creativity in Primary Education - Frans Hagerman; Shu-Nu Chang Rundgren (Ignatianum University Press, 2022)
As the world emerges from the COVID-19 pandemic and continues to struggle with armed conflicts, creative and ethical solutions to the controversial issues of recent years are needed globally. While creativity is necessary, it must also be ethically sound. Today, discussing creativity in relation to its ethical dimensions has also been emphasized in the perspective of sustainable development, but research on the teaching and learning of ethical creativity remains limited. Therefore, the aim of this paper is twofold: 1) to describe how primary schools engage students on ethical creativity and 2) to suggest a didactic model for ethical creativity based on the teaching strategies found in a literature review. Internationally, creativity and ethics have been addressed in curricula and studied within the field of education. However, research on the ethical dimensions of creativity (ethical creativity) is limited. Based on a literature review, five teaching strategies for engaging primary school students on ethical creativity have been identified. The common features among the five teaching strategies relate to the use of 1) digital tools/media, 2) art and literature, 3) real problems and dilemmas, and 4) enquiry-based learning. A three-step teaching model is suggested for teaching ethical creativity. The implications of the paper relate to enhancing ethical creativity among our children, who are both future citizens and leaders in various professions in the global society.